Privačios kariuomenės: teisinė aklavietė - Medvedevaitė, Akvilė; Meinoris, Aurelijus (Vilnius University Open Series, 2020)
War mercenaries can be traced back to the ancient era and it still survives to this day, though its form and means of use have significantly changed in the second part of the 20th century in response to changes in international law. Numerous countries nowadays are employing these modern mercenaries to replace their soldiers in many military roles. Due to the rapid spread of private military companies (PMC) and the number of contracts granted to them every year, a major concern has been raised, and until this day there are no clear international law documents that regulate the activities and define the legal status of these military contractors. Because of this, the question of PMC’s is seemingly in a grey zone of law. The main aim of this paper is to examine the trends of PMC’s, and the existing efforts to properly regulate them both on international and national levels.
Keywords: none